Prospects and challenges of the electrochemical reduction of iron oxides in alkaline media for steel production - Lopes, Daniela V.; Quina, Margarida J.; Frade, Jorge R.; Kovalevsky, Andrei V. (Frontiers in Materials, 2022)
Steelmaking industries have been facing strict decarbonization guidelines. With a net zero carbon emissions target, European policies are expected to be accomplished before 2050. Traditional steelmaking industry still operates by the carbothermic reduction of iron ores for steel production. Consequently, the steel sector is responsible for a large amount of CO2 emissions, accounting for up to 9% of the CO2 worldwide emissions. In this scope, the electrochemical reduction or electrolysis of iron oxides into metallic iron in alkaline media arises as a promising alternative technology for ironmaking. Significant advantages of this technology include the absence of CO2 emissions, non-polluting by-products such as hydrogen and oxygen gases, lower temperature against the conventional approach (~100 ºC versus 2000 ºC) and lower electric energy consumption, where around 6 GJ per ton of iron manufactured can be spared. The present minireview discusses the progress on the electrochemical reduction of iron oxides in alkaline media as a green steelmaking route. A historical overview of the global steelmaking against recent developments and challenges of the novel technology is presented, and the fundamental mechanisms of iron oxide reduction to iron and alternative iron feedstocks are discussed. Factors affecting the Faradaic efficiencies of the alkaline electroreduction of iron oxide suspensions or iron oxide bulk ceramics are also explored, focusing on the concurrent hydrogen evolution reaction. Overall, if scrutinized, this technology may become a breaking point for the steel industry sector.